Lab-Scale X-Ray Exposure Has No Measurable Impact on Lithium-Ion Battery Performance and Lifetime - Jinhong Min; Amariah Condon; Peter M. Attia (Batteries)
X-ray characterization is broadly used in battery research, development, manufacturing, and quality control. However, the impact of lab-scale X-ray exposure on battery performance and lifetime is not well understood. In this work, we evaluate the impact of lab-scale X-rays on battery performance and lifetime. We tested groups of cylindrical 18,650 cells using 2 min and 60 min X-ray imaging conditions; the performance and lifetime of these cells were identical to a control group without X-ray exposure. These results suggest that lab-scale X-ray characterization is safe for lithium-ion batteries.